Formation of giant Siberian gas emission craters (GECs) - Helge Hellevang; Mats R. Ippach; Sebastian Westermann; Mohammad Nooraiepour (Science of The Total Environment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Characterization and implications of a mass movement site in Bennu’s Bralgah Crater - Y. Tang; D.S. Lauretta; R.-L. Ballouz; D.N. DellaGiustina; A.T. Polit; M.M. Westermann; C.A. Bennett; K.J. Becker; K.J. Walsh; D.R. Golish (Icarus, 2024)

Quick guide to secondary metabolites from Apiospora and Arthrinium - Marie L. Overgaard; Trine Aalborg; Emil J. Zeuner; Klaus R. Westphal; Frederik A. Lau; Vibeke S. Nielsen; Kasper B. Carstensen; Emil A. Hundebøll; Tia A. Westermann; Gustav G. Rathsach; Jens L. Sørensen; Jens C. Frisvad; et al. (Fungal Biology Reviews, 2023)

The HDAC6/8/10 inhibitor TH34 induces DNA damage-mediated cell death in human high-grade neuroblastoma cell lines - Fiona R. Kolbinger; Emily Koeneke; Johannes Ridinger; Tino Heimburg; Michael Müller; Theresa Bayer; Wolfgang Sippl; Manfred Jung; Nikolas Gunkel; Aubry K. Miller; Frank Westermann; Olaf Witt; et al. (Archives of Toxicology, 2018)

Esperanto for histones: CENP-A, not CenH3, is the centromeric histone H3 variant - W. C. Earnshaw; R. C. Allshire; B. E. Black; K. Bloom; B. R. Brinkley; W. Brown; I. M. Cheeseman; K. H. A. Choo; G. P. Copenhaver; J. G. DeLuca; A. Desai; S. Diekmann; et al. (Chromosome Research, 2013)

Hereditary hemorrhagic telangiectasia: ENG and ALK-1 mutations in Dutch patients - T. G. W. Letteboer; R. A. Zewald; E. J. Kamping; G. de Haas; J. J. Mager; R. J. Snijder; D. Lindhout; F. A. M. Hennekam; C. J. J. Westermann; J. K. Ploos van Amstel (Human Genetics, 2005)

Some unique benefits with sudangrass for improved U.S. #1 yields and size of Russet Burbank potato - J. R. Davis; O. C. Huisman; D. T. Westermann; D. O. Everson; A. Schneider; L. H. Sorensen (American Journal of Potato Research, 2004)

Immunohistochemical Localization of Cardio-Active Neuropeptides in the Heart of a Living Fossil, Nautilus pompilius L. (Cephalopoda, Tetrabranchiata) - J. Springer; P. Ruth; K. Beuerlein; B. Westermann; R. Schipp (Journal of Molecular Histology, 2004)

Effect of repeated treatment with high doses of selegiline on behaviour, striatal dopaminergic transmission and tyrosine hydroxylase mRNA levels - Themann C.; D. Alvarez Fischer; Groß S.; Westermann R.; Weihe E.; Kuschinsky K.; Schäfer M.; Ferger B. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Sensitization to the behavioural effects of cocaine: alterations in tyrosine hydroxylase or endogenous opioid mRNAs are not necessarily involved - D. Alvarez Fischer; M.K.H. Schäfer; B. Ferger; S. Groß; R. Westermann; E. Weihe; K. Kuschinsky (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

Morphology and histology of the digestive tract of Nautilus pompilius and Nautilus macromphalus (Cephalopoda, Tetrabranchiata) - B. Westermann; R. Schipp (Zoomorphology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Nitrogen and potassium fertilization of potatoes: Sugars and starch - D. T. Westermann; D. W. James; T. A. Tindall; R. L. Hurst (American Journal of Potato Research, 1994)

Nitrogen and potassium fertilization of potatoes: Yield and specific gravity - D. T. Westermann; T. A. Tindall; D. W. James; R. L. Hurst (American Journal of Potato Research, 1994)

Nitrogen and potassium fertilization of potatoes: Evaluating nutrient element interactions in petioles with response surfaces - D. W. James; R. L. Hurst; D. T. Westermann; T. A. Tindall (American Journal of Potato Research, 1994)

Potato response to split nitrogen timing with varying amounts of excessive irrigation - J. C. Stark; I. R. McCann; D. T. Westermann; B. Izadi; T. A. Tindall (American Journal of Potato Research, 1993)

Zone-subsoiling effects on potato yield and grade - R. E. Sojka; D. T. Westermann; D. C. Kincaid; I. R. McCann; J. L. Halderson; M. Thornton (American Journal of Potato Research, 1993)

Errata - D. T. Westermann; J. R. Davis (American Journal of Potato Research, 1993)

Potato nutritional management changes and challenges into the next century - D. T. Westermann; J. R. Davis (American Journal of Potato Research, 1992)

Fertility and management practices to control verticillium wilt of the russet burbank potato - J. R. Davis; L. H. Sorensen; J. C. Stark; D. T. Westermann (American Journal of Potato Research, 1990)